The use of a wave boundary layer model in SWAN. Issue 1 (5th January 2017) - Du, Jianting; Bolaños, Rodolfo.; Guo Larsén, Xiaoli
Abstract: A wave boundary layer model (WBLM) is implemented in the third‐generation ocean wave model SWAN to improve the wind‐input source function under idealized, fetch‐limited condition. Accordingly, the white capping dissipation parameters are recalibrated to fit the new wind‐input source function to parametric growth curves. The performance of the new pair of wind‐input and dissipation source functions is validated by numerical simulations of fetch‐limited evolution of wind‐driven waves. As a result, fetch‐limited growth curves of significant wave height and peak frequency show close agreement with benchmark studies at all wind speeds (5–60 m s −1 ) and fetches (1–3000 km). The WBLM wind‐input source function explicitly calculates the drag coefficient based on the momentum and kinetic energy conservation. The modeled drag coefficient using WBLM wind‐input source function is in rather good agreement with field measurements. Thus, the new pair of wind‐input and dissipation source functions not only improve the wave simulation but also have the potential of improving air‐sea coupling systems by providing reliable momentum flux estimation at the air‐sea interface. Key Points: A wave boundary layer model is implemented in SWAN as a new wind‐input source function The WBLM is based on the momentum and kinetic energy conservation and it provides reliable wind stress estimation The new WBLM wind‐input source function improves the wave simulations in idealized fetch‐limited studies